2001
DOI: 10.1098/rspb.2000.1391
|View full text |Cite
|
Sign up to set email alerts
|

Polyploidy alters advertisement call structure in gray treefrogs

Abstract: Whole-genome duplication is believed to have played a signi¢cant role in the early evolution and diversi¢cation of vertebrate animals. The establishment of newly arisen polyploid lineages of sexually reproducing animals requires assortative mating between polyploids. Here, we show that genome duplication can directly alter a phenotypic trait mediating mate choice in the absence of genotypic change. Our results suggest that the direct e¡ect of polyploidy on behaviour is a consequence of increased cell size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(66 citation statements)
references
References 33 publications
(41 reference statements)
3
62
1
Order By: Relevance
“…Moreover, a previous study of artificially produced autotriploids of the diploid species in this complex (Hyla chrysoscelis; 2n ¼ 24) found that the pulse rate of their calls shifted in the direction of the lower values of the tetraploid species (Hyla versicolor; 4n ¼ 48) [11]. This result and a comparable study [12] of a Japanese tree frog (Hyla japonica) provide unequivocal evidence that polyploidy per se can affect behaviourally significant call properties.…”
Section: Introductionsupporting
confidence: 71%
See 3 more Smart Citations
“…Moreover, a previous study of artificially produced autotriploids of the diploid species in this complex (Hyla chrysoscelis; 2n ¼ 24) found that the pulse rate of their calls shifted in the direction of the lower values of the tetraploid species (Hyla versicolor; 4n ¼ 48) [11]. This result and a comparable study [12] of a Japanese tree frog (Hyla japonica) provide unequivocal evidence that polyploidy per se can affect behaviourally significant call properties.…”
Section: Introductionsupporting
confidence: 71%
“…Although the difference in pulse rate between diploid controls and autotriploids was only about 13 per cent in H. chrysoscelis and H. japonica [11,12], pulse rate in autotetraploids of the latter species showed a decrease of about 24 per cent [12]. A difference of this magnitude would have made possible call discrimination by both diploids (ancestral H. chrysoscelis and extinct diploid lineages) and presumably by the newly formed allotetraploids (H. versicolor) [7].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Taking this into account, the behavioral preference of females for different pulse repetition rates in di-, tri-, and tetraploid specimen of the Hyla chrysoscelis complex might be a consequence of different genome sizes, which affect cell dimensions (Keller and Gerhardt 2001;Tucker and Gerhardt 2012). Moreover, electrophysiological recordings in the torus of B. bombina (11.38 pg) with large neurons and R. temporaria (4.26 pg) with smaller neurons indicate that neurons in B. bombina do not synchronize to high stimulus pulse repetition rates as do neurons in R. temporaria (Walkowiak 1980).…”
Section: Discussionmentioning
confidence: 99%